Decomposition of Neem Leaf (Azadirachta indica A.Jus) in Hafir Doka Reserve Forest-Sudan (Global Journal of Science Frontier Research, 2018)
Litter Decomposition in forest ecosystems adds nutrients to plants, and represents a significant source of atmospheric CO 2 . Despite its essential role in carbon and nutrient cycling, leaf litter decay in reserve forest ecosystems remains poorly studied. A completely randomized block design field experiment was conducted in Hafir Doka forest reserve, (latitudes " 56 "15 015 and" 26 "15 015 N. and longitude 32º 24" 23 "̏ and 32º 13" 23 "E.). The aim of the study is to evaluate organic decomposition of neem leaf and the factors affecting it. One set of 36 litter bags each containing 20 gm. air dried neem leaf were buried 20 cm deep under the canopy of Acacia tortilis subsp. spirocarpa while another set of 36 bags were used as control, during the period November 2017-February 2018. Random samples of 14 bags were retrieved and taken to laboratory to extract their faunal contents. Soil and air temperature and soil moisture were measured during the sampling events. Decomposers fauna were extracted using Tullgern funnel. Data obtained were statistically analyzed using SPSS design at p= 0.05 and compared according to Pearson correlation coefficient. Results showed that nematodes (Aphasmida), mites (Acari: Oribatida) and Collembola (Insecta, Entomobryidae) were extracted as animal decomposers.
Keywords: neem leaf; decomposition; collembola; mites; nematodes